2019
DOI: 10.1038/s41594-019-0190-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of ligand-activated enhancers licenses cooperative chromosomal enhancer assembly

Abstract: A crucial feature of differentiated cells is the rapid activation of enhancer-driven transcriptional programs in response to signals. The potential contributions of physicochemical properties of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
247
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(261 citation statements)
references
References 71 publications
14
247
0
Order By: Relevance
“…Computational simulation has suggested that formation of these structures may promote long-range chromatin interactions 3 , and BRD4 is capable of driving clustering of acetylated chromatin in vitro 68 . In support of this, BRD4 intrinsically disordered regions (IDRs) targeted to telomeric sequences appear to bring loci together 35 and dissolution of phase condensate structures prevents the estrogen-induced colocalization of enhancers 69 . However, it is unclear how closely these observations represent physiological enhancer-promoter interactions, or whether these results are representative of mechanisms functioning generally at most enhancers.…”
Section: Discussionmentioning
confidence: 94%
“…Computational simulation has suggested that formation of these structures may promote long-range chromatin interactions 3 , and BRD4 is capable of driving clustering of acetylated chromatin in vitro 68 . In support of this, BRD4 intrinsically disordered regions (IDRs) targeted to telomeric sequences appear to bring loci together 35 and dissolution of phase condensate structures prevents the estrogen-induced colocalization of enhancers 69 . However, it is unclear how closely these observations represent physiological enhancer-promoter interactions, or whether these results are representative of mechanisms functioning generally at most enhancers.…”
Section: Discussionmentioning
confidence: 94%
“…Phase separation describes the large-scale, three-dimensional concentration of proteins and nucleic acids (Box 1) and is a means by which transcriptional machinery and multiple regulatory elements are brought together. Phase separation of enhancers has been shown at super enhancers and at enhancers utilizing the MegaTrans complex Nair et al, 2019). While much remains to be learned, the literature overall supports a model wherein eRNAs contribute to enhancer function by interacting with nuclear proteins to promote enhancer-promoter looping, chromatin modification, and regulation of transcriptional machinery, possibly through phase separation.…”
Section: Mechanisms Of Actionmentioning
confidence: 94%
“…Given the conservation of protein disorder ( Figure 1A) and recent evidence that the CTD can form and interact with phase separated droplets (Kwon et al, 2013;Chong et al, 2018;Boehning et al, 2018;Cho et al, 2018;Nair et al, 2019), we hypothesized that the function of the CTD's long disorder could be supplied by other proteins of similar chemical and structural features. We tested this idea by fusing the low complexity domains (LCD) of the human proteins FUS and TAF15, which are not present in the yeast genome, to the C-terminus of a 10CTDr truncated RPB1.…”
Section: Fusion To Disordered Proteins Can Rescue the Function Of A Cmentioning
confidence: 99%
“…CTD length has also been implicated in its ability to form (Boehning et al, 2018) and bind phase-separated droplets, with a minimum threshold that parallels its viability requirement (Kwon et al, 2013). In addition, the interaction of the CTD with these droplets can be dynamically modulated by phosphorylation (Kwon et al, 2013;Chong et al, 2018;Boehning et al, 2018;Cho et al, 2018;Nair et al, 2019), a major post-translational modification that precedes transcription initiation (Payne et al, 1989;Svejstrup et al, 1997). In light of these observations, phase separation provides an appealing framework to explain certain transcriptional phenomena.…”
Section: Introductionmentioning
confidence: 99%